Sigma-1 Receptor Chaperones and Diseases - Tsai, Shang-Yi; Hayashi, Teruo; Mori, Tomohisa; Su, Tsung-Ping (Central Nervous System Agents in Medicinal Chemistry, 2009)
Chaperones are proteins that assist the correct folding of other protein clients either when the clients are being synthesized or at their functional localities. Chaperones are responsible for certain diseases. The sigma-1 receptor is recently identified as a receptor chaperone whose activity can be activated/deactivated by specific ligands. Under physiological conditions, the sigma-1 receptor chaperones the functional IP3 receptor at the endoplasmic reticulum and mitochondrion interface to ensure proper Ca2+ signaling from endoplasmic reticulum into mitochondrion. However, under pathological conditions whereby cells encounter enormous stress that results in the endoplasmic reticulum losing its global Ca2+ homeostasis, the sigma-1 receptor translocates and counteracts the arising apoptosis. Thus, the sigma-1 receptor is a receptor chaperone essential for the metabotropic receptor signaling and for the survival against cellular stress. The sigma-1 receptor has been implicated in many diseases including addiction, pain, depression, stroke, and cancer. Whether the chaperone activity of the sigma-1 receptor attributes to those diseases awaits further investigation.
Keywords: MAM